Generational differences in psychological wellbeing and preventative behaviours among nursing students during COVID-19: a cross-sectional study. Issue 3 (4th July 2021) - Middleton, Rebekkah; Fernandez, Ritin; Moxham, Lorna; Tapsell, Amy; Halcomb, Elizabeth; Lord, Heidi; Alomari, Albara; Hunt, Leanne
Abstract : Background: Many nursing programmes have had to swiftly move online in response to COVID-19. Nursing students are often a heterogenous group that traverses generational boundaries. Exploring generational differences may assist in developing support systems for specific groups. This study sought to examine psychological wellbeing and preventative behaviours among nursing students from the iGeneration in comparison to older generations. Method: A prospective cross-sectional study was undertaken using a convenience sample of pre-registration nursing students studying at two Australian Universities, one regional and one metropolitan. About 631 pre-registration nursing students completed an online survey. Results: An independent samples t -test revealed that students from the iGeneration possess higher anxiety compared to nursing students from older generations ( p  = .000). Compared to iGeneration participants, older generation participants had significantly higher scores for knowledge of COVID-19 ( p  = .015). iGeneration participants utilised social media to source information about COVID-19 far more than older generations ( p  = .008). iGeneration participants were significantly more concerned than older generations about the impact of COVID-19 on completing their clinical placement ( p  = .014). Older generations tended to have higher academic preventative behaviours, with significant mean scores for not attending university if they or others they knew had symptoms of COVID-19. Conclusion: Given the differences between generation groups with regard to psychological wellbeing, knowledge about COVID-19, and concerns about studying in an altered study environment, strategies should be targeted to generational groups. Anxiety negatively impacts the quality of life, educational performance and clinical practice and is experienced more frequently in the iGeneration. Therefore it is crucial for nursing educators to reflect on how they engage this generation in the online space to provide support, stability and a sense of connection. This will contribute towards ensuring a well-prepared future nursing workforce who may encounter other pandemics and isolating events. Impact statement: Compared with other generations, iGeneration students have a greater likelihood to experience mental health issues, isolation and insecurity. Nursing leaders and educators must be sensitive to such intergenerational differences, to ensure they are developing a skilled and productive workforce.